Prions, prionoid complexes and amyloids: the bad, the good and something in between (Swiss Medical Weekly, 2017)
Prions are infectious agents causing transmissible spongiform encephalopathies in humans and animals. These protein-based particles template conformational changes in a host-encoded prion protein to an insoluble self-like conformation. Prions are also present in yeast, where they support protein-based epigenetic inheritance. There is emerging evidence that prion-like (prionoid) particles can support a variety of pathological and beneficial functions. The recent data on the prionoid spread of other pathological amyloids are discussed in light of differences between prions and prion-like aggregates. On the other hand, prion-like action has also been found to support important functions such as memory, and amyloids were shown to have a variety of physiological roles from storage to scaffolding in simple organisms and in humans. Higher-order protein complexes play important roles in signalling. Many death-fold domains can polymerise upon nucleation to enhance sensitivity and induce a robust response. Although these polymers are structurally different from amyloids, some of them are characterised by prionoid activities, such as intercellular spread. The initial activation of these complexes is vital for organismal health, whereas prolonged activation leading to unresolved inflammation underlies autoinflammatory and other diseases. Prionoid complexes play important roles far beyond prion diseases and neurodegeneration.